Improving human resource mobilisation for post-disaster recovery: A New Zealand case study. (January 2021) - Sun, Xuguang; Chang-Richards, Alice Yan; Kleinsman, Trent; Innes, Andrew
Abstract: New Zealand is a hazard-prone country and experiences one of the highest rates of seismic activity in the world. While a wide range of tools have been developed in previous decades to support strategic and tactical decisions for post-disaster recovery, a challenge exists in identifying critical human resources to meet the demand of post-disaster infrastructure rebuild. Based on two case studies of the 2010–2011 Canterbury earthquakes and 2016 Kaikōura earthquake, this paper aims to explore whether relevant professionals involved in the infrastructure recovery from 2010 to 2011 earthquakes were mobilised to the 2016 earthquake and what mechanisms employed and challenges faced to utilise their expertise in a systematic way. This research highlights that a gap remains in incorporating expertise and advisory capacities from the former event to the latter one due to rapid staff turnover in recovery organisations and lack of information regarding infrastructure recovery experts. Addressing these issues is important, as such expertise and advisory capacities may set the tone for disaster management and significantly impact the quality of infrastructure rebuild in New Zealand and many other countries. Highlights: Expertise and advisory capacities set the tone for post-disaster reconstruction. We examine human resource identification and mobilisation mechanisms in two earthquake events. Existing networks and relationships of disaster recovery organisations proved to be key in both cases. A gap remains in incorporating expertise and advisory capacities from one earthquake recovery to the latter. Information technology might provide solutions for improving human resource mobilisation in post-disaster recovery.